Odpowiedzi

Najlepsza Odpowiedź!
2010-02-07T18:01:57+01:00
(a)5*(4+4x+x^2)+16-x^2-2(1-2x+x^2)=20+20x+5*x^2+16-x^2-2+4x-2*x^2=2*x^22x+34
(b)4x^2+4xy+y^2-3x^2-3y^2+6xy+4x^2-9y^2=5x^2-11y^2+10xy
(c) a^3-2a^2+4a-8-a^3-4a^2-4a-4a^2+12a-9=-10a^2+12a-17
(d) (3m+2n)(3m+2n-3m+2n)-(m^4+2*n*m^2+n^2)+(m^2+n^2+2mn)= 12mn+8n^2-m^4-2*n*m^2-n^2+m^2+n^2+2mn=14mn+8n^2-m^4-2*n*m^2+m^2
2010-02-07T18:13:40+01:00
Zad.13
a) 5(2+x)²+(4-x)(4+x)-2(1-x)²=5(4+4x-x²)+(16-x²)-2(1-2x+x²)=20+20x+5x²+16-x²-2+4x-2x²=2x²+24x+34

b) (2x-y)²-3(x-y)²+(-2x-3y)(-2x+3y)=
4x²-4xy+y²-3(x²-2xy+y²)+4x²-9y²=4x²-4xy+y²-3x²+6xy-3y²+4x²-9y²=
5x²-11y²+2xy

c) (n-2)³-a(a+2)³-(2n-3)²=n³-6n²+12n-8-a(a³+6a²+12a+8)-4n²-12n+9=
n³-6n²+12n-8-a⁴-6a³-12a²-8a-4n²-12n+9=-a⁴-6a³-12a²-8a+n³-10n²+1